Characterization and quantification of biochar alkalinity. (January 2017) - Fidel, Rivka B.; Laird, David A.; Thompson, Michael L.; Lawrinenko, Michael
Abstract: Lack of knowledge regarding the nature of biochar alkalis has hindered understanding of pH-sensitive biochar-soil interactions. Here we investigate the nature of biochar alkalinity and present a cohesive suite of methods for its quantification. Biochars produced from cellulose, corn stover and wood feedstocks had significant low-pKa organic structural (0.03–0.34 meq g −1 ), other organic (0–0.92 meq g −1 ), carbonate (0.02–1.5 meq g −1 ), and other inorganic (0–0.26 meq g −1 ) alkalinities. All four categories of biochar alkalinity contributed to total biochar alkalinity and are therefore relevant to pH-sensitive soil processes. Total biochar alkalinity was strongly correlated with base cation concentration, but biochar alkalinity was not a simple function of elemental composition, soluble ash, fixed carbon, or volatile matter content. More research is needed to characterize soluble biochar alkalis other than carbonates and to establish predictive relationships among biochar production parameters and the composition of biochar alkalis. Graphical abstract: Highlights: We present a suite of methods for quantifying biochar alkalinity in four categories. Total biochar alkalinity and distribution of alkalis varied widely among biochars. Base cation concentration was a good predictor of total biochar alkalinity. Inorganic alkalis comprised >55% of lignocellulosic biochar alkalinity.